Relationship between Family Support and Patient Attitudes with Compliance of Pulmonary TB Patients Carrying Out Final Follow-Up of Treatment at the Health Center - Tia Agustina Mardi; Andi Parellangi; Edi Purwanto (PT FORMOSA CENDEKIA GLOBAL, 2023)
The final follow-up of pulmonary TB treatment is monitoring the regularity and adherence of patient treatment. This study aims to determine the relationship between family support, patient attitudes and adherence of pulmonary TB patients to follow-up at the end of treatment at the Berau District Health Center. This study uses a correlational analytic research design with a cross-sectional approach. The population of 99 people was carried out by purposive sampling technique. The standard instruments used in this study were a family support questionnaire from Yani Arnoldus, a patient attitude questionnaire from Alif Arditia.Y and adherence to follow-up at the end of treatment using an adherence questionnaire using MMAS-8, and continued filling out the questionnaire. The data obtained were then analyzed univariately and bivariately with the Chi Square test. Obtained the variable values of family support and compliance of pulmonary TB patients following up at the end of treatment with p-value = 0.001, which is below α = 0.05 (p <α = 0.05), and the attitude variable with adherence of pulmonary TB patients following up at the end of treatment with p-value = 0.580 which is above α = 0.05 (p > α = 0.05). So it can be concluded that there is a relationship between family support and adherence of pulmonary TB patients to follow up at the end of treatment and there is no significant relationship between patient attitudes and compliance of pulmonary TB patients to follow up at the end of treatment at the Puskesmas.